Selective Autophagy of the Protein Homeostasis Machinery: Ribophagy, Proteaphagy and ER-Phagy - Beese, Carsten J.; Brynjólfsdóttir, Sólveig H.; Frankel, Lisa B. (Frontiers in Cell and Developmental Biology, 2020)
The eukaryotic cell has developed intricate machineries that monitor and maintain proteome homeostasis in order to ensure cellular functionality. This involves the carefully coordinated balance between protein synthesis and degradation pathways, which are dynamically regulated in order to meet the constantly changing demands of the cell. Ribosomes, together with the endoplasmic reticulum (ER), are the key drivers of protein synthesis, folding, maturation and sorting, while the proteasome plays a pivotal role in terminating the existence of thousands of proteins that are misfolded, damaged or otherwise obsolete. The synthesis, structure and function of these dedicated machines has been studied for decades, however, much less is understood about the mechanisms that control and execute their own turnover. Autophagy, an evolutionarily conserved catabolic pathway, mediates degradation of a large variety of cytosolic substrates, ranging from single proteins to entire organelles or multi-subunit macromolecular complexes. In this review, we focus on selective autophagy of three key components of the protein homeostasis machinery: ribosomes, ER and proteasomes, through the selective autophagy pathways of ribophagy, ER-phagy and proteaphagy. We discuss newly discovered mechanisms for the selective clearance of these substrates, which are often stress-dependent and involve specialized signals for cargo recognition by a growing number of receptors. We further discuss the interplay between these pathways and their biological impact on key aspects of proteome homeostasis and cellular function in health and disease.